Estudo de métodos de coleta e análise de metano em gás de mina de carvão subterrânea - Kuckartz, Silvia Fernanda Rodrigues Viégas (2014)
With low cost and still abundant, fossil coal remains a source of energy used worldwide. The gases emitted during the extraction of coal, generally consist of mixtures of methane, carbon dioxide, nitrogen dioxide and other hydrocarbons. However, methane is the most emitted in proportion. The use of natural gas as fuel is advantageous from an environmental point of view and has become economically attractive. The collection of gas samples is still a problem faced in related coal mine gas studies. Some products known as Tedlar® sampling bags for example, are efficient but, they have some drawbacks. In this work we tested an alternative means to collect gaseous samples, Vacutainers®. For identification and quantification of gases (CH4, CO2 and CO), analyses of gas chromatography with flame ionization detector were performed. Gaseous samples from the air of underground mines and waste piles of coal, in addition to standard mixtures, were analyzed after different periods of storage using Vacutainer® container type collectors. These collectors compared to Tedlars® were not efficient for the quantification of real samples containing CH4 and CO2. However, when accepting a 5 % error, it was effective for CO found in real samples. Results related to the concentration of CH4 in coal mine showed a concentration ranging from 117 ppm to 1,8 %, indicating a potential recovery and use of this gas as an energy source. On the other hand, alert to the need of periodic monitoring in order to ensure safety in the mine